Lysosomal Oxidative Stress Cytotoxicity Induced by Dacarbazine and It’s Pyridine Derivative in Hepatocytes: Dacarbazine induced lysosomal oxidative stress - Pourahmad, Jalal; Kobarfard, Farzad; Amirmostofian, Marzieh (Iranian Journal of Pharmaceutical Sciences, 2006)
Dacarbazine (DTIC) is a synthetic chemical antitumor agent which is used to treat malignant melanoma and Hodgkin’s disease. DTIC is a prodrug which is converted to an active form undergoing demethylation by liver enzymes. The active form prevents the progress of disease via alkylation of DNA strand. In the structure of this drug, the imidazole ring, a triazen chain and carboxamide group exist. Based on the literature, the ring and carboxamide group do not have a key role in antitumor activity of the drug. On the other hand, imidazole ring has a unique tautomerization which may participate in the mechanism of action of DTIC and carboxamide group may determine the rich guanine pieces in DNA strand. In order to investigate the mechanistic role of imidazole group and its known tautomerization in DTIC cytotoxicity, derivative of DTIC with a pyridine ring (3-(3,3-dimethyl-1-triazenyl)pyridine, (compound I) instead of imidazole ring was synthesized. In the following, the cellular and molecular mechanism of cytotoxicity induced by DTIC and its pyridine derivative toward the isolated rat hepatocytes were studied and compared. Hepatocyte reactive oxygen species (ROS) generation was significantly increased by both DTIC and compound B before cytotoxicity ensued. In addition, DTIC and compound I induced lysosomal damage and hepatocyte protease activation. Endocytosis inhibitors, lysosomotropic agents or lysosomal protease inhibitors also prevented both DTIC and compound B induced hepatocytes cytotoxicity. Furthermore desferoxamine (a ferric chelator), antioxidants or ROS scavengers (catalase, mannitol or dimethylsulfoxide) prevented both DTIC and compound I cytotoxicity. It is concluded that H2O2 reacts with lysosomal Fe2+ to form hydroxyl radical which (Haber-Weiss reaction) causes lysosomal membrane disruption, proteases and other digestive enzymes release and finally the cell death.